Whole genome phylogenetic investigation of a West Nile virus strain isolated from a tick sampled from livestock in north eastern Kenya - Lwande, Olivia Wesula; Venter, M.; Lutomiah, J.; Michuki, George N.; Rumberia, C.; Gakuya, F.; Obanda, V.; Tigoi, C.; Odhiambo, C.; Nindo, F.; Symekher, S.; Sang, R. (Springer, 2014)
Background West Nile virus (WNV) has a wide geographical distribution and has been associated to cause neurological disease in humans and horses. Mosquitoes are the traditional vectors for WNV; however, the virus has also been isolated from tick species in North Africa and Europe which could be a means of introduction and spread of the virus over long distances through migratory birds. Although WNV has been isolated in mosquitoes in Kenya, paucity of genetic and pathogenicity data exists. We previously reported the isolation of WNV from ticks collected from livestock and wildlife in Ijara District of Kenya, a hotspot for arbovirus activity. Here we report the full genome sequence and phylogenetic investigation of their origin and relation to strains from other regions. Methods A total of 10,488 ticks were sampled from animal hosts, classified to species and processed in pools of up to eight ticks per pool. Virus screening was performed by cell culture, RT-PCR and sequencing. Phylogenetic analysis was carried out to determine the evolutionary relationships of our isolate. Results Among other viruses, WNV was isolated from a pool of Rhipicephalus pulchellus sampled from cattle, sequenced and submitted to GenBank (Accession number: KC243146). Comparative analysis with 27 different strains revealed that our isolate belongs to lineage 1 and clustered relatively closely to isolates from North Africa and Europe, Russia and the United States. Overall, Bayesian analysis based on nucleotide sequences showed that lineage 1 strains including the Kenyan strain had diverged 200 years ago from lineage 2 strains of southern Africa. Ijara strain collected from a tick sampled on livestock was closest to another Kenyan strain and had diverged 20 years ago from strains detected in Morocco and Europe and 30 years ago from strains identified in the USA. Conclusion To our knowledge, this is the first characterized WNV strain isolated from R. pulchellus. The epidemiological role of this tick in WNV transmission and dissemination remains equivocal but presents tick verses mosquito virus transmission has been neglected. Genetic data of this strain suggest that lineage 1 strains from Africa could be dispersed through tick vectors by wild migratory birds to Europe and beyond.